Ethical disclosure of biomarkers for Alzheimer risk in Latin American participants - Oviedo, Diana C.; Haughbrook, Rasheda; Culjat, Carli; Ramirez Surmeier, Ladanya; Tratner, Adam E.; Carreira, María B.; Villarreal, Alcibiades E.; Harmon, Sherelle L.; Batista, Oriana I.; Meng, Zhuo; Millender, Eugenia; Xavier Hall, Casey D.; et al. (Frontiers in Dementia, 2025)
IntroductionIn recent years, the disclosure of Alzheimer’s disease (AD) biomarkers has become increasingly common, offering critical insights into disease risk and progression. However, in low-resource settings, where healthcare access, provider training, and patient support are often limited, disclosing AD biomarkers presents unique ethical, logistical, and psychological challenges.ObjectiveThis perspective explores the implications of AD biomarker disclosure in these settings, highlighting the potential risks of patient distress, misinformation, and inadequate follow-up care. For this purpose, we conducted a review of available literature, peer-reviewed studies, regional reports, and policy documents addressing AD in Latin America. Our literature search prioritized diagnostic advances, biomarker disclosure, treatment access, and health system challenges, providing a focused evidence base to frame the discussion of regional gaps and opportunities.DiscussionWe discuss strategies to support responsible disclosure practices, including culturally sensitive participant education, enhanced provider training, and policy adaptations to improve accessibility and support systems. Ultimately, we advocate for a careful, context-specific approach to AD biomarker disclosure that prioritizes patient well-being and equity in low-resource environments.